A study in using rice husk as an additive to cast polyurethane resin in silicone vacuum casting - N. H., Hassan; M. N., Adanan; N. M., Zain; M., Ibrahim (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology (MUCEET) 2009 organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis, 20th - 22nd June 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.